Antibiotic usage pattern among inpatients of a paediatric ward in a tertiary care hospital in Eastern India - Mukherjee, Shatavisa; Sen, Sukanta; Era, Nikhil; Biswas, Arunava; Datta, Kalpana; Tripathi, Santanu K. (International Journal of Research in Medical Sciences, 2017)
Background: The inevitable consequence of the widespread use of antimicrobial agents has been the emergence of antibiotic resistant pathogens. The rising incidence of bacterial resistance to common antibiotics, particularly, multi-drug resistant pneumococci, has prompted the need to use antibiotics judiciously in paediatric practice. The present study thus attempted to understand the antibiotic usage pattern among inpatients in a paediatric ward of a tertiary care hospital. Methods: A cross-sectional study was carried out for three months among the inpatients in the Department of Pediatrics in a tertiary care teaching hospital, Kolkata. The data regarding patient’s demographics and antibiotic use was collected daily in a pre-structured proforma. A descriptive statistical analysis of the data was performed. Results: A total of 124 patients were screened of which males and females represented 58.06% and 41.94% of the cases respectively with age group of 2-14 years presenting in majority. Among various causes of hospitalization, prevalence of respiratory disorders were maximum (25.81%), followed by hematological disorders (25%). Among various categories of prescribed drugs, antibiotics were found to be maximum (39.25%). Beta-lactum antibiotics were prescribed in majority (64.41%) with 56.91% being of cephalosporin group. The preferred route of administration was found to be parenteral (64%). 61.29 % cases were ordered laboratory investigations prior to the antimicrobial therapy initiation. About 63.16% of the total samples for culture & sensitivity tested were reported positive. 39.58% of these positive cases showed resistance to empirical antibiotic therapy on lab reports. Conclusions: The study enables to obtain information on the antibiotic usage pattern in the pediatric population, focusing on prevalence of antibiotic misuse in our set-up and suggesting strategies of its minimization.